(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article explores the legal foundations and primary objectives of accounting processes, focusing on the automation and integration of information technologies to enhance the efficiency of managerial functions in various economic sectors. It examines the specific features of informatization, computerization, and automation of accounting in modern business environments. The study highlights the advantages of automated accounting systems over traditional methods and discusses widely used computer programs in practical accounting activities. The findings emphasize the role of automated systems in optimizing accounting processes and improving decision-making efficiency.